Evidence-Based Case Report: The Prevention and Management of Postherpetic Neuralgia With Emphasis on Interventional Procedures. Issue 5 (1st August 2009) - Benzon, Honorio T.; Chekka, Kiran; Darnule, Amit; Chung, Brian; Wille, Oscar; Malik, Khalid
Abstract : Objective: A patient with postherpetic neuralgia (PHN) did not respond to medications, either singly or in combination, or to intrathecal methylprednisolone but responded to intrathecal alcohol. This evidenced-based case management article evaluates and grades the evidence for the prevention and treatment of PHN. Methods: A search of published English-language studies on the prevention and treatment of PHN was made. Results: Randomized clinical studies showed the efficacy of antiviral agents in the prevention of PHN and the use of anticonvulsants, antidepressants, opioids, and Lidoderm patch in the treatment of PHN (level A evidence). The role of epidural local anesthetic and steroid injections in preventing PHN has not been completely established (level B evidence). Intrathecal steroid injections and topical capsaicin may be effective in PHN (level B evidence). No randomized controlled study supports the usefulness of spinal cord stimulation and intrathecal alcohol. Conclusions: Postherpetic neuralgia should be managed pharmacologically. If not effective, intrathecal steroid injections or nerve blocks may be tried. Spinal cord stimulation or intrathecal alcohol should be used only as a last resort.